Iron Mobility During Diagenesis at Vera Rubin Ridge, Gale Crater, Mars. Issue 11 (13th November 2020) - L'Haridon, J.; Mangold, N.; Fraeman, A. A.; Johnson, J. R.; Cousin, A.; Rapin, W.; David, G.; Dehouck, E.; Sun, V.; Frydenvang, J.; Gasnault, O.; Gasda, P.; et al.
Abstract: The Curiosity rover investigated a topographic structure known as Vera Rubin ridge, associated with a hematite signature in orbital spectra. There, Curiosity encountered mudstones interpreted as lacustrine deposits, conformably overlying the 300 m‐thick underlying sedimentary rocks of the Murray formation at the base of Mount Sharp. While the presence of hematite (α‐Fe2 O3 ) was confirmed in situ by both Mastcam and ChemCam spectral observations and by the CheMin instrument, neither ChemCam nor APXS observed any significant increase in FeOT (total iron oxide) abundances compared to the rest of the Murray formation. Instead, Curiosity discovered dark‐toned diagenetic features displaying anomalously high FeOT abundances, commonly observed in association with light‐toned Ca‐sulfate veins but also as crystal pseudomorphs in the host rock. These iron‐rich diagenetic features are predominantly observed in "gray" outcrops on the upper part of the ridge, which lack the telltale ferric signature of other Vera Rubin ridge outcrops. Their composition is consistent with anhydrous Fe‐oxide, as the enrichment in iron is not associated with enrichment in any other elements, nor with detections of volatiles. The lack of ferric absorption features in the ChemCam reflectance spectra and the hexagonal crystalline structure associated with dark‐toned crystals points toward coarse "gray" hematite. In addition, the host rock adjacent to these features appears bleached and shows low‐FeOT content as well as depletion in Mn, indicating mobilization of these redox‐sensitive elements during diagenesis. Thus, groundwater fluid circulations could account for the remobilization of iron and recrystallization as crystalline hematite during diagenesis on Vera Rubin ridge. Plain Language Summary: The NASA rover Curiosity investigated Vera Rubin ridge, a specific landform within the Gale crater on Mars. Scientific missions in orbit around the planet had previously discovered high concentrations of hematite on top of the ridge, an iron‐oxide mineral that commonly forms in water. However, it was not clear from orbit if such conditions existed at the time of the deposition of the sediments (around 3.5 billion years ago) or occurred much later during "diagenesis, " after deposition of the sediments and up to their transformation into rocks. On the surface, the rover did not observe significant differences between the ridge and the terrains encountered before it, except for small, dark geologic features that formed during diagenesis. Their analysis by the ChemCam instrument revealed that these features are composed of hematite—the same iron‐oxide mineral that was observed from orbit—and, interestingly, that the iron required to form them was removed from the adjacent rocks by groundwaters. As such, it appears that groundwaters played an important role in shaping Vera Rubin ridge, and thus partially obscure interpretations on the environmental conditions that existed on the surface of Mars at the time of sedimentation. Key Points: Images from the Curiosity rover show the presence of dark‐toned diagenetic features at Vera Rubin ridge ChemCam analyses of these features point toward an Fe‐oxide composition, consistent with crystalline hematite Depletion of Fe and Mn in bleached halos around the Fe‐oxide features indicates mobility of Fe and Mn during the later stages of diagenesis